Trazodone, dibenzoylmethane and tauroursodeoxycholic acid do not prevent motor dysfunction and neurodegeneration in Marinesco-Sjögren syndrome mice. - Giada Lavigna; Anna Grasso; Chiara Pasini; Valentina Grande; Laura Mignogna; Elena Restelli; Antonio Masone; Claudia Fracasso; Jacopo Lucchetti; Marco Gobbi; Roberto Chiesa (PLoS ONE)
There is no cure for Marinesco-Sjögren syndrome (MSS), a genetic multisystem disease linked to loss-of-function mutations in the SIL1 gene, encoding a BiP co-chaperone. Previously, we showed that the PERK kinase inhibitor GSK2606414 delays cerebellar Purkinje cell (PC) degeneration and the onset of ataxia in the woozy mouse model of MSS. However, GSK2606414 is toxic to the pancreas and does not completely rescue the woozy phenotype. The present study tested trazodone and dibenzoylmethane (DBM), which partially inhibit PERK signaling with neuroprotective effects and no pancreatic toxicity. We also tested the chemical chaperone tauroursodeoxycholic acid (TUDCA), which protects MSS patients' cells from stress-induced apoptosis. Mice were chronically treated for five weeks, starting from a presymptomatic stage. Trazodone was given 40 mg/kg daily by intraperitoneal (ip) injection. DBM was given 0.5% in the diet ad libitum. TUDCA was given either 0.4% in the diet, or 500 mg/kg ip every three days. None of the treatments prevented motor dysfunction or PC degeneration in woozy mice, as assessed by beam walking, rotarod test, and calbindin immunohistochemistry. Only trazodone slightly boosted beam walking performance, but this effect was not related to inhibition of PERK signaling. Pharmacokinetic studies excluded that the lack of effect was due to altered drug metabolism in woozy mice. These results indicate that trazodone, DBM and TUDCA, at dosing regimens active in other neurodegenerative disease mouse models, have no disease-modifying effect in a preclinical model of MSS. This underscores the difficulty of translating neuroprotective strategies from other conditions to MSS, highlighting the need for more targeted therapeutic approaches.